USING MOVIES TO IMPROVE THE STUDENTS SPEAKING SKILL AT THE THIRD SEMESTER OF EARLY CHILDHOOD EDUCATION DEPARTMENT OF STKIP PAHLAWAN TUANKU TAMBUSAI - Lusi Marleni (Universitas Pahlawan Tuanku Tambusai, 2016)
The t h i r d s e m e s t e r students o f Early Childhood Education Department of STKIP Pahlawan Tuanku Tambusai Riau had problem in speaking E n g l i s h . The purpose of this research is to improve the students speaking skill and also to know the factors influence the students speaking skill. The participants of this research are 22 students of the third semester of the Early Childhood Education Department of STKIP Pahlawan Tuanku Tambusai Riau. The research is classroom action research which was done in two cycles with four meetings. Each cycle consists of plan, action, observation, and reflection. The result of this study shows that using movies in teaching and learning English can improve the students speaking skill. Based on the data, the mean score of the students speaking skill as well as the increasing of the mean score of speaking skill indicators namely accent, grammar, vocabulary, fluency, and comprehension. The average score was 60 in pre research, 66.3 in cycle I, and 71.4 in cycle II. The factors that influenced the students speaking skill are material, media, classroom activity, classroom management, teachers approach, and teachers strategy. It means, there is improvement on the students speaking skill.